MORPHOLOGY OF THE DURAL SINUSES OF THE BRAIN - Tirkashev Abduvahid Sharof o‘g‘li; Kamalova Malika Ilkhomovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Based on the literature review, clarified the main stages of development of the sinuses of the Dura mater of the brain in the antenatal period of development. Data on the sinus Dura brain is aligned with the international anatomical terminology. The process in which undifferentiated venous network consolidates in the venous sinuses and large veins of the brain, explains most of the numerous variants and anomalies of extracerebral veins. Knowledge of the development of the sinuses of the Dura mater of the brain facilitates the understanding of many anatomical facts.